Strategi Penanganan Konflik Kepemimpinan Non-Muslim di Birokrasi: Studi Kasus di Kecamatan Pajangan, Bantul, Yogyakarta - Angkat, Ismail (Universitas Nurul Jadid, 2019)
Abstract: The purpose of this research is to know the factors underlying the conflict about the Pajangan sub-district in Bantul, and how to resolution conflicts involving the Pajangan sub-district by the government and the community. The informants in this study were mass organizations, civil society, community leaders, traditional leaders, and security forces in Pajangan District related to these cases. The research used in this research is descriptive qualitative research. The results of this study reveal the facts that occurred in the Pajangan sub-district was motivated by several factors in it is the socialization of the government related to the policy of setting the Pajangan sub-district head. The government is less open to the public regarding the policies issued. The policies issued by the government are not quite right. The policy is not in accordance with the culture of the people in the Display, although the Regent's policy does not violate the laws and regulations for the election of the camat. In addition, the community also understands the Regent's policy that can consider the cultural conditions in Pajangan, especially the people in Pajangan which are full of Muslims, and also supports the differences which are the main reason for the Pajangan community to reject the camat. The government and the community have taken several actions to resolve the conflict over the conflict, such as negotiation, mediation, and finally arbitration.Keywords: Leadership, Non-Muslim, and Bureaucracy